Thin and flexible Mg0.7Ni0.3Fe2O4 nanoparticle-reinforced chitosan/polyvinyl alcohol bionanocomposite films with tunable dielectric properties for energy storage devices - Misirlioglu, Banu Sungu; Berber, Hale; Gul, Ecem; Oladipo, Akeem Adeyemi; Gazi, Mustafa (ELSEVIER, 2026)
The development of flexible, eco-friendly materials is critical for next-generation energy storage devices. Herein, novel bionanocomposite films were fabricated by dispersing non-stoichiometric Mg0.7Ni0.3Fe2O4 spinel ferrite nanoparticles (up to 20 wt%) into a chitosan/polyvinyl alcohol (CS/PVA) matrix. A comprehensive analysis of the structure-property relationships was performed. The incorporation of nanoparticles resulted in a trade-off in mechanical properties: while tensile strength decreased from 56.5 MPa to 13.4 MPa, flexibility was greatly enhanced, with elongation at break increasing by 270 % (from 2.35 % to 8.75 %). Thermogravimetric analysis confirmed improved thermal stability, with the main polymer degradation temperature increasing by over 20 degrees C. The dielectric properties were dramatically enhanced due to Maxwell-Wagner-Sillars polarization, with the dielectric constant (epsilon') at 10 Hz surging from 25.7 to 7433.9. Correspondingly, the AC conductivity at 1 kHz increased by over two orders of magnitude. The composites demonstrated pseudocapacitive behavior, achieving a maximum specific capacitance of 40.7 F/g and an energy density of 0.19 Wh/kg for the 20 wt% film. Spectroscopic and microscopic analyses confirmed that strong interfacial interactions between the well-dispersed nanoparticles and the polymer matrix were responsible for these enhancements. This work demonstrates that incorporating engineered ferrite nanoparticles into a biopolymer matrix is a highly effective strategy for creating flexible, high-performance dielectrics for sustainable energy storage applications.
Keywords: Chitosan; Bionanocomposite; Dielectric property; Ferrite nanoparticle; Mechanical property; POLYMER ELECTROLYTES; SIZE; PERFORMANCE; BATIO3; Biochemistry & Molecular Biology; Chemistry; Polymer Science